Why is There Something Rather Than Nothing? A Probabilistic Answer Examined. (29th June 2018) - Rodriguez-Pereyra, Gonzalo
Abstract: Peter van Inwagen has given an answer to the question 'Why is there something rather than nothing?'. His answer is: Because there being nothing is as improbable as anything can be: it has probability 0. Here I shall examine his argument for this answer and I shall argue that it does not work because no good reasons have been given for two of the argument's premises and that the conclusion of the argument does not constitute an answer to the question van Inwagen wanted to answer.